Foreign Arbitration As The Only Recourse In Resolving Trademark Disputes In A Civil Manner, Criticism of Act Number 20 Year 2016 About Brands and Geographical Indications - Narwadan, Theresia Nolda Agnes (Fakultas Hukum Universitas Pattimura, 2024)
Introduction: Act Number 20 year 2016 on trademark and geographic indication opens up opportunities to resolve trademark disputes not only through the Commercial Court, but also to resolve disputes through the District Court.Purposes of the Research: The purpose of the study was to find a form of fair trademark dispute resolution. Conventionally, dispute resolution is usually done by litigation or dispute resolution before the court.Methods of the Research: Normative research is used to answer the formulation of problems regarding foreign arbitration as the only way to resolve trademark rights disputes in a civil manner. The method of approach is the approach of legislation that is to examine and analyze the regulation.Results of the Research: Indonesia also has repeatedly updated the regulation on trademark, but on the other hand, the level of trademark infringement is increasing, even the Commercial Court which should be a place for people to seek justice often gives decisions that do not reflect justice. Is it not better to start looking for other alternatives to resolve trademark disputes that can provide a sense of justice to the community. The court, which is only a mouthpiece of the acts, without regard to the conventions in the field of trademark that have actually been ratified by Indonesia, making the enforcement of trademark regulations in Indonesia, has not been able to provide a sense of justice to holders of rights to trademarks, especially holders of rights to well-known trademars. So that the settlement of famous brand disputes through foreign arbitration is expected to provide a sense of justice for the rights holders of the wellknown trademark.